Oesophagectomy: The expanding role of minimally invasive surgery in oesophageal cancer. (October 2018) - van den Berg, J.W.; Luketich, J.D.; Cheong, E.
Abstract: Historically, open oesophagectomy was the gold standard for oesophageal cancer surgery. This was associated with a relatively higher morbidity. In the last two decades, we have seen significant improvements in short and long term outcomes due to centralisation of oesophagectomy, multidisciplinary approach, enhanced recovery after surgery programmes, neoadjuvant treatments and advances in minimally invasive oesophagectomy (MIO) techniques. MIO has significantly reduced postoperative morbidity and improved functional recovery, while maintaining comparable long-term oncological outcomes. MIO is technically demanding, and requires a long learning curve. However, it has been proven to be safe and successful in expert centres. This is a review on the current role of MIO in the management of oesophageal cancer.